Radiographic Views of Digestive Tracts of Rainbow Trout (Oncorhynchus Mykiss) and Mirror Carp (Cyprinus Carpio) - Çalta, Metin (Fırat University, 2016)
In this study, radiographic views of digestive tracts of rainbow trout [Oncorhynchus mykiss (Walbaum, 1792)] and mirror carp (Cyprinus carpio Linnaeus, 1758) were investigated. For this purpose, barium sulphate suspension was used as contrast agent. This agent was given into fish digestive tracts from the anus using a syringe. Then X-ray radiographs of fishes were taken. It was found that there were quite big differences between rainbow trout and mirror carp in term of structure of digestive tract. In comparison, digestive tract of rainbow trout is shorter because of possessing short intestine, anatomic stomach and pyloric caeca are present. However, digestive tract of mirror carp is very longer because of possessing long intestine and anatomic stomach is absent.

Bu çalışmada, gökkuşağı alabalığı [Oncorhynchus mykiss (Walbaum, 1792)] ve aynalı sazan (Cyprinus carpio Linnaeus, 1758)’da sindirim kanalının radyografik görünümleri incelendi. Bu amaçla, kontrast madde olarak baryum sülfat süspansiyonu kullanıldı. Bu madde bir şırınga yardımıyla anüsten sindirim kanalına verildi. Daha sonra balıkların X-ışını radyografileri alındı. Sindirim kanalı yapısı bakımından gökkuşağı alabalığı ve aynalı sazan arasında oldukça büyük fark olduğu tespit edildi. Yapılan karşılaştırmada, gökkuşağı alabalığı sindirim kanalının bağırsakların kısalığından dolayı daha kısa olduğu, anatomik mide ve plorik çekumların mevcut olduğu belirlendi. Buna karşılık, aynalı sazanda bağırsakların uzun olmasından dolayı sindirim kanalının da daha uzun olduğu ve anatomik midenin olmadığı görüldü.
Gökkuşağı Alabalığı (Oncorhynchus Mykiss) ve Aynalı Sazan (Cyprinus Carpio)’da Sindirim Kanalının Radyografik Görüntülenmesi